ORIENTASI NILAI DAN GERAKAN MASYARAKAT PRO-KONSERVASI DI INDOENSIA (Value Orientation and Pro-Conservation Community Movement in Indonesia) - Didik Suharjito (Media Konservasi, 2008)
Some researches on environmental concern, environmental awareness, and environmental behavior had been conducted. Research on environmental value orientation of citizen, especially in term of State law-based value had not been deeply done. Research on this issue is very relevant and important to be done, moreover in a multicultural society such as Indonesia in which the State legal orders or national laws become the reference for her citizen’s behavior. The author’s purposes were to explain (1) what was the Indonesian’s environmental value orientation, pro or contra environmental conservation? That value orientation was explained by analyzing government policies especially those which stated in the national laws; and (2) how to transform pro-conservation value orientation and attitudes into real conservation behavior in their daily life. The author concluded that Indonesian people’s value orientation of natural (forest) resources was anthropocentrism value. Indonesian people had pro-conservation concern in term of anthropocentrism ideology oriented conservation movement. In contrast, Indonesian people were against conservation which based upon ecocentrism/biocentrism ideology. The author suggested that GREM was appropriate for Indonesian context. Efforts needed to transform pro-conservation orientation value into behavior were (1) enhancing stakeholders including all category and class of community, central-province-district government; (2) realizing collective action involving stakeholders through developing ideology or value (i.e. GERM) as behavior reference; facilitative, innovative, wide-view leadership; strengthening trust, reciprocation, support, sharing, and synergy among stakeholders.Keywords: environmental awareness, environmental values orientation, environmental movement, new environmental paradigm.